Engagement in online entertainment: A preliminary study among adolescents in Klang Valley / Ana Afrina Abd Jamil, Yarina Ahmad and Ahmad Naqiyuddin Bakar - Abd Jamil, Ana Afrina; Ahmad, Yarina; Bakar, Ahmad Naqiyuddin (2021)
Entertainment consumption is not new as our ancestors in general too spent their spare time for leisure, and some are common with today's entertainment such as sports, board games, swimming, and going to theatres (Fife, 2012). This paper focuses on online entertainment, which can be accessed through various gadgets and smart gadgets available today, such as smartphones, smart television, laptops, tablets, and many more. Types of online entertainment, platforms, the content available for access are manifold. In Malaysia, the smartphone internet users who engage in entertainment activities make up the majority with activities such as watching videos and movies, play games, and listen to music; are those below 20 years of age with the percentage of 88.4%, 92.3%, and 73.9% respectively (MCMC, 2019). The recent pandemic COVID-19 has caused a considerable loss to the media and entertainment industry with a surging drop of 55% followed by zero sales; ironically, it also causing changes in viewers behaviour drove a spike and demands for diversity and discretion from viewers makes the growth of entertainment platforms to increase too (Mizal, 2021).